2017
DOI: 10.1111/gcb.13620
|View full text |Cite
|
Sign up to set email alerts
|

Extreme rainfall and snowfall alter responses of soil respiration to nitrogen fertilization: a 3‐year field experiment

Abstract: 26Extreme precipitation is predicted to be more frequent and intense accompanying global 27 warming, and may have profound impacts on soil respiration (Rs) and its components, i.e., 28 autotrophic (Ra) and heterotrophic (Rh) respiration. However, how natural extreme rainfall or 29 snowfall events affect these fluxes are still lacking, especially under nitrogen (N) fertilization. 30In this study, extreme rainfall and snowfall events occurred during a 3-year field experiment,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 85 publications
2
30
0
Order By: Relevance
“…The AP7 explained 24%-37% (mean: 31%) and 28%-38% (mean: 35%) of the temporal variations in R s on the TG and BF hillslopes, respectively. Positive relationships between R s and precipitation were also found by Chen et al [13] and Zhou et al [8], while some other studies demonstrated that increased precipitation could reduce R s due to the slow gas diffusion [15,42]. In this study, the relative lower explanation rates (<30%) of AP7 on R s in TG-03, BF-03, and BF-04 were due to the wet soil conditions at these sites ( Table 2).…”
Section: Factors Influencing R S Response To Precipitationsupporting
confidence: 75%
See 3 more Smart Citations
“…The AP7 explained 24%-37% (mean: 31%) and 28%-38% (mean: 35%) of the temporal variations in R s on the TG and BF hillslopes, respectively. Positive relationships between R s and precipitation were also found by Chen et al [13] and Zhou et al [8], while some other studies demonstrated that increased precipitation could reduce R s due to the slow gas diffusion [15,42]. In this study, the relative lower explanation rates (<30%) of AP7 on R s in TG-03, BF-03, and BF-04 were due to the wet soil conditions at these sites ( Table 2).…”
Section: Factors Influencing R S Response To Precipitationsupporting
confidence: 75%
“…Liu et al [11] found that at extremely high ST (e.g., >28 • C), R s declined due to insufficient SWC. Carey et al [12] reported a universal decline in the temperature sensitivity (Q 10 ) of R s with ST > 25 • C, and this result may be due to low SWC at high ST. Precipitation influences R s through two related mechanisms: one is stimulating the exchanges of substrates and gases in soil pores by rain dripping; the other is improving the connectivity of substrates through increasing SWC [11,13]. Generally, increased precipitation has a positive effect on R s [8,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequent occurrence of rainfall extremes produces multiple disasters, including urban flooding, server soil erosion, landslides and debris flows [1]. Moreover, rainfall extremes affect the ecological process of the terrestrial ecosystem [2,3]. The spatial patterns of extreme precipitation trends exhibit heterogeneous characteristics, especially at a smaller scale, due to factors including warming, water vapor trends and topography differences [4,5].…”
Section: Introductionmentioning
confidence: 99%